(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
Saline stress is a condition that causes changes in physiological performance in several species and even in cultivars of the same species. Thus, this study aimed to evaluate the physiological performance of black bean cultivars to salt stress. A completely randomized experimental design was used in a factorial scheme with two cultivars (Mataço and BRS Paisano) and five osmotic potentials simulated with sodium chloride solutions (control = 0.0; -0.2; -0.4; -0.6 and -0.8 MPa), in four replications of 50 seeds per treatment. The variables related to germination, first germination count, germination speed index, and shoot length were evaluated. There were significant interactions (p <0.05) for all variables analyzed. In general, it is concluded that the physiological performance of the seeds of black bean cultivars is affected under simulated saline stress by NaCl solution with an osmotic potential below -0.2 MPa.